Analisis Kode Etik Akuntan Dalam Penyajian Laporan Keuangan PT XYZ - ayu, dewi; Hadmanti, Tiara; Supriadi, Iman (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2021)
As one of the important pillars of the business sector is profession must have a high moral commitment and usually all of this is stated in the form of special rules that serve as guidelines for everyone who develops the profession concerned. The object of this research is the ethics of the accountant profession in the presentation of financial statements at PT XYZ which is company engaged in the construction sector. There are several problems faced by construction entrepreneurs during the current pandemic, such as intense business competition between entrepreneurs, presentation of financial statements that must be in accordance with the target of shareholders both internal and external to the company, to unstable sales results that sometimes go up and down. , and besides that there are many internal and external factors that can affect the company's profit. From these problems, this construction company also involved manipulation of financial statements by PT XYZ. Therefore, it is necessary to have ethics and strategies in the accounting profession that will be the right solution to overcome these problems that arise. This study uses descriptive qualitative research methods. The method used is descriptive qualitative approach with data analysis techniques, then this research results in the formulation of an effective and efficient professional ethics strategy to develop business in this construction sector. The alternative strategy formulated is the ethics of accountants in the presentation of financial statements that are appropriate and in accordance with the regulations currently in force.